ABC-CBA=CAB

Simple and best practice solution for ABC-CBA=CAB equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ABC-CBA=CAB equation:


Simplifying
ABC + -1CBA = CAB
Combine like terms: ABC + -1ABC = 0
0 = CAB
Solving
0 = ABC
Solving for variable 'A'.
Move all terms containing A to the left, all other terms to the right.
Add '-1ABC' to each side of the equation.
0 + -1ABC = ABC + -1ABC
Remove the zero:
-1ABC = ABC + -1ABC
Combine like terms: ABC + -1ABC = 0
-1ABC = 0
Divide each side by '-1'.
ABC = 0
Simplifying
ABC = 0
The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 7x+33=8x-18 | | 2k^2-8k+6=0 | | -14x+2[3-2(x+6)]= | | 4.3x-2.9+x-2.3= | | 19x^2-13x=12 | | 11pr=7920 | | (350-10a)(a-21)=400 | | 2b-5-11b-8= | | 5x-60=2x | | 7.2x-4.7=62.3 | | x+0.76x=446725.79 | | Ln(2x+3)+ln(x-7)-2lnx=0 | | w+14=l | | y=11-4(-2) | | -3x+3[2-2(-3x+2)]= | | 7p-q-5=0 | | -25+104-17=142 | | 2(y-5)-(y-3)=2 | | 4g-2g-2=50 | | X+5x-2=0 | | (y-5)-(y-3)=2 | | 82m-83m+6m=60 | | h=16t^2+54+40 | | 46g-7g+13g+6g-54g-4=84 | | 11x+20=12x+5 | | 7x+6x-3x= | | 7m^2-61m-18=0 | | 4c+12=7c+10.68 | | -47p+59p-21p=99 | | 4x^2+88x+336=0 | | 7r^2+72r+20=0 | | -6w+-2w=64 | | 11n-7n-2n+7=45 | | 6n-11=4n-15 | | -4g+-14g+4g-25=17 | | .5y+10=y+4 | | 160+2x=208+(-3x) | | -8x+2[x-(4-5x)]= | | 2v^2-2V+40=v^2+16 | | 26g-30g=24 | | -17+x-9=2-42+8 | | 14+x=20+2x | | 14+x=20+-2x | | 16g-14g=18 | | 2(x+3)=x+y | | 4x-6=2x+11 | | n^2+n+1=3 | | 4x-6=x+11+x | | X-8.7=-6.2 | | 14x+20=96-242 | | -4(2v-2)=8(-2v+14)+6v | | 15p-13p+61p-p=128 | | 21x^2+10x-16= | | 21=4-5x | | 81xsquared+126x+49=0 | | 2(7s+8)-5s=3(3s+1)-5 | | N+4+6n=3+8n | | 6x+5y=y | | 18s^2=2s | | X=((1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4)(1+1.4))-1 | | 144=3x(x) | | p=3x(x) | | 2x*-2x=1 | | -200,000-80,000x=-3600,000 | | x=(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14)(0.14) |


Related pages


what is the greatest common factor of 120find the greatest common factor calculatorfind the prime factorization of 9log100square root of 1458derivative of cos y9x squared5280 x 3b 2 4acy 2sin2xmdt solutionx2 4xxy xyzprime factorization of 300e 4x derivativewhat is the gcf of 72 and 96derivativ calculatorbx12gcf of 84common multiples of 91939 in roman numeralsq mcdeltatsolve x 2 2x-4 0square root 43560www.cosex.tk12u7what is the gcf of 56 and 98secx move5x 7 2xsquare root of 1681factorization calculatorsquare root 676subtracting fractions calculator show worknforc5.75 as a fraction3.0914x2 3x 1800-528y 2y 3 9log3x 4prime factorization of 936y 9 3 2y 31 cosx sinxderiviative calculatorsimplify 2x 5log1001-cos4x3y x 30.35 as a decimal100-743x derivativewhat is 7x3easy equation solverfind the prime factorization of 120find the prime factorization of 300roman numerals 1992cos3x sin3xprime factorization 300kt v formula1800-130091.1xmultiples of 323whats 8x7solve y 2x 3simplify and combine like terms calculatorsolve 2x2 12x 103z2derivative ln x 36yigcf generator37.5 as a fractionsinx cosgreatest factor calculatorprime factorization of 400solve for x ax bx ccos x cos 2x